Racial Differences in the Incidence of Colorectal Cancer - Rukinder Virk; Sharlene Gill; Eric Yoshida; Simon Radley; Baljinder Salh (Canadian Journal of Gastroenterology)
BACKGROUND: Colon cancer is one of the most common cancers and the second most common cause of cancer mortality in Western societies. Population screening has been introduced as a means to reducing its impact; however, there are little or no data on the incidence of this disorder in the different populations that comprise the Canadian population.